Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

What is the Laplace transform of this function? $$f(x)=\frac{\sqrt{x}}{1+x}$$

share|cite|improve this question
Maybe just go from the definition? I don't really see any clever way to do it. How far have you gotten? Have you tried the substitution $\sqrt x = t$ to see where that goes? – Scaramouche Jan 14 '12 at 8:47
According to the Wolfram Alpha result is : $\sqrt{\frac{\pi}{s}}-\pi \cdot e^s \cdot erfc(\sqrt{s})$ , where erfc is complementary error function... – pedja Jan 14 '12 at 8:55
up vote 6 down vote accepted

We want $\displaystyle F(t)=\int^{\infty}_0 \frac{\sqrt{x}}{1+x} e^{-t x} dx$

$F(t) e^{-t}=\int^{\infty}_0 \frac{\sqrt{x}}{1+x} e^{-t(x+1)} dx$
$\frac{d}{dt}(F(t) e^{-t})=-\int^{\infty}_0 \sqrt{x}e^{-t(x+1)} dx$
$e^t\frac{d}{dt}(F(t) e^{-t})=-\int^{\infty}_0 \sqrt{x}e^{-tx} dx=-t^{-1/2-1}\Gamma(1/2+1)=-\sqrt{\pi}/(2t^{\frac32})$
because you got a specific case of the integral defining the Gamma function.

After that you'll have to revert the operations :
$F(t)= -\frac{\sqrt{\pi}}2 e^t \left(C+\int \frac{e^{-t}}{t\sqrt{t}} dt\right)$
$F(t)= -\frac{\sqrt{\pi}}2 e^t \left(C-\frac{2e^{-t}}{\sqrt{t}}-\int \frac{2e^{-t}}{\sqrt{t}} dt\right)$
$F(t)= -\frac{\sqrt{\pi}}2 e^t \left(C-\frac{2e^{-t}}{\sqrt{t}}-2\int e^{-u^2} du\right)$
where we recognize the integral expression of the Error function multiplied by $\sqrt{\pi}$.

I'll let you reverify all this and determine the constant $C$.

The answer should be $\sqrt{\frac{\pi}{t}} -\pi e^t \text{ erfc}(\sqrt{t})$ for $\Re(t)\gt0$ (with $\text{erfc}(x)=1-\text{erf}(x)$).

(short way : Wolfram Alpha).

share|cite|improve this answer
Thank you for your answer! – robert Jan 14 '12 at 12:01

$$ f(t)=\frac{\sqrt{t}}{1+t} $$ $$ (1+t)f(t)=\sqrt{t} $$ $$ \downarrow {\mathcal{L}} $$ $$ F(s)-\frac{d}{ds}F(s)=\frac{\frac{\sqrt{\pi}}{2}}{s^{\frac{3}{2}}} $$ we have First Order Differential Equation: $$ \frac{d}{ds}F(s)-F(s)=-\frac{\frac{\sqrt{\pi}}{2}}{s^{\frac{3}{2}}} $$ We know : $$ \dfrac{dy}{dt}+ P(t) y = Q(t) \space , \space y=e^{-\int P(t)dt} \left[\int Q(t) e^{\int P(t)dt} dt+c \right] $$ So : $$ F(s)=e^{-\int (-1)ds}\left[ \int \frac{\frac{-\sqrt{\pi}}{2}}{s^{\frac{3}{2}}}e^{\int(-1)ds}ds+C \right] $$ $$ F(s)=e^s \left[ (\frac{-\sqrt{\pi}}{2}) \int \frac{1}{s^{\frac{3}{2}}} e^{-s} ds +C\right] $$ $$ F(s)=e^s \left[ (\frac{-\sqrt{\pi}}{2}) \left( \frac{-2e^{-s}}{\sqrt{s}} -2\sqrt{\pi} .Erf (\sqrt{s}) \right) +C \right]$$ $$ F(s)=\sqrt{\frac{\pi}{s}}+\pi e^s.Erf(\sqrt{s})+Ce^s $$

share|cite|improve this answer
+1. Good attempt Amir. ;-) – Babak S. Dec 22 '12 at 18:13

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.